Susceptibility of Field-Collected Aedes aegypti (L.) (Diptera: Culicidae) to Bacillus thuringiensis israelensis and temephos - Loke, S.R.; Andy-Tan, W.A.; Benjamin, S.; Lee, H.L.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2010)
The susceptibility status of field-collected Aedes aegypti (L.) from a dengue endemic area to Bacillus thuringiensis israelensis (Bti) and temephos was determined. Since August 2007, biweekly ovitrap surveillance (OS) was conducted for 12 mo in 2 sites, A & B, in Shah Alam, Selangor. Site A was treated with a Bti formulation, VectoBacÂ® WG at 500 g/ha, from December 2007 - June 2008 while Site B was subjected to routine dengue vector control activities conducted by the local municipality. Aedes aegypti larvae collected from OS in both sites were bred until F3 and evaluated for their susceptibility. The larvae were pooled according to 3 time periods, which corresponded to Bti treatment phases in site A: August - November 2007 (Bti pre-treatment phase); December 2007 - June 2008 (Bti treatment phase); and July - September 2008 (Bti post-treatment phase). Larvae were bioassayed against Bti or temephos in accordance with WHO standard methods. Larvae collected from Site A was resistant to temephos, while incipient temephos resistant was detected in Site B throughout the study using WHO diagnostic dosage of 0.02 mg/L. The LC 50 of temephos ranged between 0.007040 - 0.03799 mg/L throughout the year in both sites. Resistance ratios (LC 50) indicated that temephos resistance increased with time, from 1.2 - 6.7 folds. The LC 50 of Ae. aegypti larvae to Bti ranged between 0.08890 - 0.1814 mg/L throughout the year in both sites, showing uniform susceptibility of field larvae to Bti, in spite of Site A receiving 18 Bti treatments over a period of 7 mo. No cross-resistance of Ae. aegypti larvae from temephos to Bti was detected.